A stochastic assembly model for Nipah virus revealed by super-resolution microscopy - Qian Liu (Nature Portfolio, 2018)
The current model for Nipah virus assembly suggests that packaging is orchestrated by the matrix protein at the plasma membrane. Here, using super-resolution microscopy and Nipah virus-like particles, Liu et al. show that Nipah virus assembly is stochastic.